1998
DOI: 10.1038/bjc.1998.244
|View full text |Cite
|
Sign up to set email alerts
|

Initial high anti-emetic efficacy of granisetron with dexamethasone is not maintained over repeated cycles

Abstract: Initial high antimemetic efficacy of granisetron with dexamethasone is not maintained over repeated cycles R de Wit', H van den Berg', J Burghouts2, J Nortier3, P Slee4, C Rodenburg5, J Keizer6, M Fonteyn7, J Verweij1 and J Wils7 Summary We have reported previously that the anti-emetic efficacy of single agent 5HT3 antagonists is not maintained when analysed with the measurement of cumulative probabilities. Presently, the most effective anti-emetic regimen is a combination of a 5HT3 antagonist plus dexamethaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 11 publications
1
26
0
2
Order By: Relevance
“…Conversely, failure during the acute period has a high negative predictive value for delayed 190 emesis in the same cycle [12]. Furthermore, patients who experience delayed symptoms during their initial cycle of chemotherapy are more likely to suffer recurrent delayed symptoms during subsequent cycles [13] as well as reduced acute antiemetic protection in the next cycle [30]. Thus, any patient characteristic that predisposes an individual to acute symptoms (such as female sex, low prior alcohol intake history, and emesis with prior cycles of chemotherapy) should also be considered as a predictive factor for delayed nausea and vomiting [11].…”
Section: Correlation Between Acute and Delayed Control Of Cinvmentioning
confidence: 99%
“…Conversely, failure during the acute period has a high negative predictive value for delayed 190 emesis in the same cycle [12]. Furthermore, patients who experience delayed symptoms during their initial cycle of chemotherapy are more likely to suffer recurrent delayed symptoms during subsequent cycles [13] as well as reduced acute antiemetic protection in the next cycle [30]. Thus, any patient characteristic that predisposes an individual to acute symptoms (such as female sex, low prior alcohol intake history, and emesis with prior cycles of chemotherapy) should also be considered as a predictive factor for delayed nausea and vomiting [11].…”
Section: Correlation Between Acute and Delayed Control Of Cinvmentioning
confidence: 99%
“…(6,7) In several clinical studies of a 5-HT 3 receptor antagonist with dexamethasone, no efficacy was demonstrated for CINV in the delayed phase. (3,8) Aprepitant is a neurokinin-1 (NK 1 ) receptor antagonist developed as a treatment for CINV.…”
mentioning
confidence: 99%
“…In the largest study in 125 patients receiving six cycles of cisplatin-based chemotherapy, despite dual therapy with granisetron and dexamethasone both in the acute and the delayed period, the initial complete acute emesis protection decreased from 66 to 39%, and for delayed emesis, the initial complete protection of 52% decreased to 43, or 21% in the sixth cycle, depending on the type of statistical analysis. In this study, it was also found that unsuccessful delayed emesis protection adversely influenced acute emesis protection in subsequent cycles of chemotherapy (de Wit et al, 1998). If delayed emesis protection is not improved, most patients will develop emesis, and in due course both in the acute and in the delayed phase.…”
Section: Ht 3 Antagonists Antiemetic Efficacy Is Not Maintained Overmentioning
confidence: 55%
“…Several studies have demonstrated that indeed, and despite the use of 5HT 3 antagonist plus dexamethasone, with each subsequent cycle of chemotherapy, emesis protection decreases (de Wit et al, , 1998. In the largest study in 125 patients receiving six cycles of cisplatin-based chemotherapy, despite dual therapy with granisetron and dexamethasone both in the acute and the delayed period, the initial complete acute emesis protection decreased from 66 to 39%, and for delayed emesis, the initial complete protection of 52% decreased to 43, or 21% in the sixth cycle, depending on the type of statistical analysis.…”
Section: Ht 3 Antagonists Antiemetic Efficacy Is Not Maintained Overmentioning
confidence: 99%
See 1 more Smart Citation